Commercialising Public Research under the Open Innovation Model: New Trends - Mario Cervantes; Dirk Meissner (Foresight and STI Governance, 2014)
Public research plays an extremely important role in social and economic development, and has implications for industry, services, education, training, the creation and diffusion of knowledge, management etc. In turn, R&D and innovation activities in the business sector are becoming increasingly open. Being influenced by increasingly tightened global competition, companies are entering into partnerships with other companies, universities or public research institutions (PRIs) to leverage competences from different places and organizations to foster innovation. The search for partners and the management of many co-operations itself are new challenges especially in terms of administering intellectual property rights. Universities and PRIs must respond to the changing requirements imposed by companies while maintaining their unique positions as research and science related institutions. The overall framework conditions for these actors are changing, which in turn requires new government policies especially given the slowdown in key performance indicators of the commercialization activities of PRIs.